2021
DOI: 10.1021/acs.jpclett.0c03292
|View full text |Cite
|
Sign up to set email alerts
|

Vibrational Motions Make Significant Contributions to Sequential Methyl C–H Activations in an Organometallic Complex

Abstract: [(Pentamethylcyclopentadienyl)­Rh­(III)­(bipyridine)­(chloride)]+ (Cp*Rh–Cl) undergoes sequential deuteriation of its 15 Cp* CH groups in polar deuterated solvents. Vibrational spectra of H 14 –Cp*Rh–Cl and D 14 -Cp*Rh–Cl were captured via inelastic neutron spectroscopy (INS) and assigned using density functional theory (DFT) phonon calculations. These calculations were precisely weighted to the spectrometer’s neutronic response. The Cp* ring behaves as a moving carousel, bringing each CH3 close to the Rh–… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 23 publications
1
10
0
Order By: Relevance
“…Here we see a mix of intra-molecular and inter-molecular vibrations, methyl rotations, and phonons. This area of the spectrum elucidates much of the bonding properties of the system [29,30], but gives limited information on the delocalised motion of each atom. For these less localised motions, we must use the technique of Quasi-elastic Neutron Spectroscopy (QENS).…”
Section: And Neutron Scatteringmentioning
confidence: 99%
“…Here we see a mix of intra-molecular and inter-molecular vibrations, methyl rotations, and phonons. This area of the spectrum elucidates much of the bonding properties of the system [29,30], but gives limited information on the delocalised motion of each atom. For these less localised motions, we must use the technique of Quasi-elastic Neutron Spectroscopy (QENS).…”
Section: And Neutron Scatteringmentioning
confidence: 99%
“…12) for proton transfer between Rh-OH hydroxide and Cp X methyl groups for complex 1, calculated for the models involving a methanol molecule compared to those obtained for the model assuming purely intramolecular (no methanol molecule involved). 15…”
Section: Dalton Transactions Papermentioning
confidence: 99%
“…This has yet to be achieved for previously reported molecular machines. 28,29 Our initial vibronic studies 15 have revealed that vibrations are crucial for the reaction pathways, particularly, the conversion of local vibrations into translational motion for progression along the reaction coordinate, and for weakening bonds in the transition state, so lowering the vibrational energy.…”
Section: Dalton Transactions Papermentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the past decade has witnessed a very rapid increase in the quantity and quality of combined in-silico and INS studies, giving unprecedented clarity to a range of chemical phenomena at the atomic scale [4,5,6]. Some examples include the understanding of phase transitions [7,8,9], quantifying the role of vibrations to the kinetics in catalytic processes [10] and gas absorption in porous media [11].…”
Section: Introductionmentioning
confidence: 99%